The second victim experience: cross-cultural adaptation of an instrument for the Brazilian context - Luisa Petelincar De Sordi; Daniela Campos de Andrade Lourenção; Cristiane Helena Gallasch; Patrícia Campos Pavan Baptista (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective To cross-culturally adapt and analyze the evidence of content validity of the Second Victim Experience and Support Tool for the Portuguese language spoken in Brazil. Method Psychometric study of cross-cultural adaptation following the steps of the Patient-Reported Outcome Measurement Information System. Semantic, idiomatic, experimental, and conceptual equivalences were evaluated. The content validity was verified using the Content Validity Ratio. 31 health professionals from the city of São Paulo participated in the pre-test. Results The equivalence analysis showed an agreement rate was 88.7%. The content validity presented 86% of the items with Content Validity Ratio values above the stipulated. In the pre-test, the participants reported that they understood the items of the instrument and only 10% of the participants reported difficulty in understanding any item. Conclusion The Brazilian version of the Second Victim Experience and Support Tool presented a good translation quality and good evidence of content validity.